Complete chloroplast genome sequence and phylogenetic analysis of Spathiphyllum 'Parrish'. - Xiao-Fei Liu (PLoS ONE, 2019)
Spathiphyllum is a very important tropical plant used as a small, potted, ornamental plant in South China, with an annual output value of hundreds of millions of yuan. In this study, we sequenced and analyzed the complete nucleotide sequence of the Spathiphyllum 'Parrish' chloroplast genome. The whole chloroplast genome is 168,493 bp in length, and includes a pair of inverted repeat (IR) regions (IRa and IRb, each 31,600 bp), separated by a small single-copy (SSC, 15,799 bp) region and a large single-copy (LSC, 89,494 bp) region. Our annotation revealed that the S. 'Parrish' chloroplast genome contained 132 genes, including 87 protein coding genes, 37 transfer RNA genes, and 8 ribosomal RNA genes. In the repeat structure analysis, we detected 281 simple sequence repeats (SSRs) which included mononucleotides (223), dinucleotides (28), trinucleotides (12), tetranucleotides (11), pentanucleotides (6), and hexanucleotides (1), in the S. 'Parrish' chloroplast genome. In addition, we identified 50 long repeats, comprising 18 forward repeats, 13 reverse repeats, 17 palindromic repeats, and 2 complementary repeats. Single nucleotide polymorphism (SNP) and insertion/deletion (indel) analyses of the chloroplast genome of the S. 'Parrish' relative S. cannifolium revealed 962 SNPs in S. 'Parrish'. There were 158 indels (90 insertions and 68 deletions) in the S. 'Parrish' chloroplast genome relative to the S. cannifolium chloroplast genome. Phylogenetic analysis of five species found S. 'Parrish' to be more closely related to S. kochii than to S. cannifolium. This study identified the characteristics of the S. 'Parrish' chloroplast genome, which will facilitate species identification and phylogenetic analysis within the genus Spathiphyllum.